1998
DOI: 10.1038/bjc.1998.85
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of integrins in vitro and in vivo in uveal and cutaneous melanomas

Abstract: Summary Changes in integrin expression have been shown to be important for the growth and metastatic capacity of melanoma cells. In this study, we have examined the expression of av integrins by three uveal and four cutaneous malanoma lines. No lines expressed avP6 and only TXM1 3, a cutaneous line, expressed av,B8. All lines expressed avf5 and avP3 (four out of four cutaneous, two out of three uveal) or avfi1 (OM431, an uveal line). Thus, OM431 is the second uveal melanoma we have described that expresses avI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 37 publications
5
16
0
Order By: Relevance
“…Many studies have revealed that the expression of integrins is frequently changed during melanoma development. Moreover, up-regulation of integrin expression is accompanied by displaying a more metastatic phenotype [58]. Based on these data, we assume that mast cell-derived serotonin has a major impact on malignant melanoma cell behaviour.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have revealed that the expression of integrins is frequently changed during melanoma development. Moreover, up-regulation of integrin expression is accompanied by displaying a more metastatic phenotype [58]. Based on these data, we assume that mast cell-derived serotonin has a major impact on malignant melanoma cell behaviour.…”
Section: Discussionmentioning
confidence: 97%
“…Upregulation of their expression has been associated with increased malignancy of melanoma cells (Marshall et al, 1998). TNF-a induced upregulation of integrin expression could be a critical step in the invasion of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…In brief, there are two theories to explain how melanoma cells invade through ECM proteins. One requires that there is increased migration of melanoma cells along ECM proteins (Marshall et al, 1998), the other that melanoma cells degrade the matrix proteins to migrate through them (Bodey et al, 2001). In practice, it is almost certainly the case that both will occur in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, upregulation of integrin expression is associated with the acquisition of a more metastatic phenotype [14]. As to human melanoma, several of these ECM receptors have been found to be dysregulated mainly in primary and metastatic cells.…”
Section: Expression Pattern Of Integrins In Malignant Melanomamentioning
confidence: 99%